Lauric Acid Is an Inhibitor of Clostridium difficile Growth in Vitro and Reduces Inflammation in a Mouse Infection Model - Yang, Hsiao-Ting; Chen, Jenn-Wei; Rathod, Jagat; Jiang, Yu-Zhen; Tsai, Pei-Jane; Hung, Yuan-Pin; Ko, Wen-Chien; Paredes-Sabja, Daniel; Huang, I-Hsiu (Frontiers in Microbiology, 2018)
Clostridium difficile is a gram-positive, spore-forming anaerobic human gastrointestinal pathogen. C. difficile infection (CDI) is a major health concern worldwide, with disease symptoms ranging from diarrhea, pseudomembranous colitis, toxic megacolon, sepsis, and death. CDI onset and progression are mostly manifested based on intestinal dysbiosis and exposure to C. difficile spores. Current treatment strategies rely on antibiotic usage, which can often result in high recurrence rates and might increase the risk of developing antibiotic-resistant strains. Medium-chain fatty acids (MCFAs) have been revealed to inhibit the growth of multiple human bacterial pathogens. Previously, components of coconut oil, which included lauric acid, were revealed to inhibit C. difficile growth in vitro. Here we demonstrated that lauric acid exhibits potent antimicrobial activities against multiple toxigenic C. difficile isolates in vitro. The mechanisms of inhibition are due partly to the generation of the reactive oxygen species (ROS) and cell membrane damage. Biofilm formation and preformed biofilm were also considerably reduced by the administration of lauric acid in a dose-dependent manner. Importantly, in a murine infection model, lauric acid pretreatment lessened CDI symptoms and reduced proinflammatory cytokine production. Our combined results suggest that naturally occurring MCFA lauric acid is a novel C. difficile inhibitor, and could be useful in the development of an alternative or adjunctive treatment for CDI.